The UX book : process and guidelines for ensuring a quality user experience - Hartson, Rex (Morgan Kaufmann, 2012)
This is a comprehensive textbook on designing interaction to ensure a quality user experience. Combining breadth, depth, and practical applications, this book takes a time-tested process-and-guidelines approach that provides readers with actionable methods and techniques while retaining a firm grounding in HCI concepts and theory. The authors will guide you through the UX lifecycle process, including contextual inquiry and analysis, requirements extraction, design ideation and creation, practical design production, prototyping, and UX evaluation. Development activities are linked via handoffs between stages as practitioners move through the process. The lifecycle template concept introduced in this book can be tailored to any project environment, from large enterprise system development to commercial products. Students and practitioners alike will come away with knowledge and understanding of how to create and refine interaction designs to ensure a quality user experience. For more information see theuxbook.com *A very broad approach to user experience through its components-usability, usefulness, and emotional impact with special attention to lightweight methods such as rapid UX evaluation techniques and an agile UX development process *Universal applicability of processes, principles, and guidelines-not just for GUIs and the Web, but for all kinds of interaction and devices: embodied interaction, mobile devices, ATMs, refrigerators, and elevator controls, and even highway signage *Extensive design guidelines applied in the context of the various kinds of affordances necessary to support all aspects of interaction *Real-world stories and contributions from accomplished UX practitioners *A practical guide to best practices and established principles in UX *A lifecycle template that can be instantiated and tailored to a given project, for a given type of system development, on a given budget.
Keywords: User interfaces (Computer systems); elektronické knihy; electronic books